PENGARUH CONTENT MARKETING DAN ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP KEPUTUSAN PEMBELIAN DI RUMAH MAKAN SAUNG SUNDARA TIGARAKSA KABUPATEN TANGERANG - Farhan Oktav; Siti Aprilliani (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to determine the partial and simultaneous effects of Content Marketing and Electronic Word of Mouth (E-WOM) on Purchase Decisions at Rumah Makan Saung Sundara. This research employed a descriptive quantitative method with a sample of 100 respondents. The data analysis techniques used included validity testing, reliability testing, normality testing, multicollinearity testing, heteroscedasticity testing, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t-test, and F-test. Based on the results of the first hypothesis test, Content Marketing has a positive and significant effect on Purchase Decisions, with a t of 4.483 greater than the t value of 1.98447 (4.483 > 1.98447) and a significance value of 0.001 less than 0.05 (0.001 < 0.05). The results of the second hypothesis test indicate that Electronic Word of Mouth (E-WOM) has a positive and significant effect on Purchase Decisions, with a t of 6.182 greater than the t value of 1.98447 (6.182 > 1.98447) and a significance value of 0.001 less than 0.05 (0.001 < 0.05). The results of the third hypothesis test show that Content Marketing and Electronic Word of Mouth (E-WOM) simultaneously have a positive and significant effect on Purchase Decisions, with an F of 44.799 greater than the F value of 3.09 (44.799 > 3.09) and a significance value of 0.001 less than 0.05 (0.001 < 0.05).